Chronic Low-Level Lead Exposure Increases Mesenteric Vascular Reactivity: Role of Cyclooxygenase-2-Derived Prostanoids - Simões, Maylla Ronacher; Azevedo, Bruna Fernandes; Alonso, María Jesús; Salaices, Mercedes; Vassallo, Dalton Valentim (Frontiers in Physiology, 2021)
Acute and chronic lead (Pb) exposure may cause hypertension and other cardiovascular diseases. Our purpose was to evaluate the effects of Pb chronic exposure on peripheral vascular resistance measuring the vascular reactivity of mesenteric resistance arteries in rats and to elucidate the mechanisms involved in the development of Pb-induced hypertension. Mesenteric resistance arteries from untreated and lead-treated Wistar rats (1 st dose: 10 μg/100 g; subsequent doses: 0.125 μg/100 g, intramuscular, 30 days) were used. Contractile responses to phenylephrine increased, while acetylcholine and sodium nitroprussideinduced relaxation was not affected by lead treatment. Endothelium removal and NO synthase inhibition by L-NAME similarly enhanced the response to phenylephrine in untreated and lead-treated rats. The antioxidants apocynin and superoxide dismutase (SOD) did not affect vasoconstriction in either group. The vascular expression of cyclooxygenase-2 (COX-2) protein increased after lead exposure. The respective non-specific or specific COX-2 inhibitors indomethacin and NS398 decreased more strongly the response to phenylephrine in treated rats. Antagonists of EP1 (SC19220), TP (SQ29548), IP (CAY10441) and angiotensin II type 1 (losartan) receptors reduced vasoconstriction only in treated rats. These findings offer further evidence that even in small concentration, lead is hazardous and might be an environmental contaminant that account for leadinduced hypertension.